Dayak Traditional Music Extracurricular Learning Strategy at SMP Negeri 03 Pontianak - Oktaviani, Oktaviani; Olendo, Yudhistira Oscar; Putra, Zakarias Aria Widyatama (Universitas Tanjungpura, 2024)
SMP Negeri 03 Pontianak's traditional music extracurricular programme has achieved a great deal. The traditional music processed and prepared for the province level competition is performed by a Dayak instrument group. The success of the Festival Lomba Siswa Seni Nasional (FLS2N) number one achievement is inextricably linked to the learning methodologies used by educators. The purpose of this study is to present the learning technique for Dayak traditional music extracurricular activities at SMP Negeri 03 Pontianak. The research technique employed was descriptive, combining a case study and qualitative approach. Data were gathered by observation, in-depth interviews with two experts, and documentation. Data validity was achieved using source triangulation procedures and member checks in the last stage, which involved data analysis via condensation, distribution, verification, and conclusion drafting. The study found that four learning styles are used during the Dayak traditional music instruction process: expository, demonstration, problem-based, and collaborative. Furthermore, the teacher's function as a motivator is to encourage students' success in achieving their goals by providing excitement and arousing students' confidence in their ability to win. The implication of this research is that it can provide additional references for cultural arts teachers to have special strategies in order to obtain the desired goals and achievements.